Analyze the Merdeka Curriculum Policy in Relation to the Implementation of Student – Centered Learning (SCL) as a Means of Improving the Quality of Islamic Education - Sukron Jamil; Helmiati; Hariza Hasyim (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This article aims to analyze the merdeka curriculum policy in relation to the implementation of student-centered learning (SCL) as a means of improving the quality of Islamic education. The study focuses on how problem-based learning (PBL), project-based learning (PjBL), and deep learning models can be integrated into the context of madrasahs and pesantren, while also examining their implications for cognitive, affective, and psychomotor competencies, the strengthening of Islamic character, and the development of 21st-century skills. The research method employed is a literature study using content analysis techniques. Data were collected from various academic sources, including books, journal articles, and relevant research findings. The analysis process involved selecting, categorizing, comparing, and synthesizing information from these sources to obtain a comprehensive picture of the merdeka curriculum implementation.The findings indicate that the merdeka curriculum provides a policy direction that supports student-centered learning through curriculum flexibility, diagnostic assessment, and the project for strengthening the Pancasila Student Profile. The application of SCL in Islamic education has proven effective in enhancing critical thinking, creativity, collaboration, and communication skills, while also deepening the internalization of Islamic values. Nevertheless, several challenges remain, such as teacher readiness, limited facilities, and the persistence of traditional learning cultures. In conclusion, the merdeka curriculum holds great potential to improve the quality of Islamic education, provided it is supported by teacher capacity building, adequate facilities, and comprehensive evaluation. With consistent implementation, Islamic education can produce graduates who are not only academically competent but also possess strong Islamic character and are well-prepared for the demands of the 21st century.